4-Heteroaryl Substituted Amino-3,5-Dicyanopyridines as New Adenosine Receptor Ligands: Novel Insights on Structure-Activity Relationships and Perspectives - Daniela Catarzi; Flavia Varano; Erica Vigiani; Sara Calenda; Fabrizio Melani; Katia Varani; Fabrizio Vincenzi; Silvia Pasquini; Natascia Mennini; Giulia Nerli; Diego Dal Ben; Rosaria Volpini; et al. (Pharmaceuticals, 2022)
A new set of amino-3,5-dicyanopyridines was synthesized and biologically evaluated at the adenosine receptors (ARs). This chemical class is particularly versatile, as small structural modifications can influence not only affinity and selectivity, but also the pharmacological profile. Thus, in order to deepen the structure–activity relationships (SARs) of this series, different substituents were evaluated at the diverse positions on the dicyanopyridine scaffold. In general, the herein reported compounds show nanomolar binding affinity and interact better with both the human (h) A1 and A2A ARs than with the other subtypes. Docking studies at hAR structure were performed to rationalize the observed affinity data. Of interest are compounds 1 and 5, which can be considered as pan ligands as binding all the ARs with comparable nanomolar binding affinity (A1AR: 1, Ki = 9.63 nM; 5, Ki = 2.50 nM; A2AAR: 1, Ki = 21 nM; 5, Ki = 24 nM; A3AR: 1, Ki = 52 nM; 5, Ki = 25 nM; A2BAR: 1, EC50 = 1.4 nM; 5, EC50 = 1.12 nM). Moreover, these compounds showed a partial agonist profile at all the ARs. This combined AR partial agonist activity could lead us to hypothesize a potential effect in the repair process of damaged tissue that would be beneficial in both wound healing and remodeling.